Probing the electronic structure of ether functionalised ionic liquids using X-ray photoelectron spectroscopy. Issue 3 (2nd January 2020) - Dick, Ejike J.; Fouda, Adam E. A.; Besley, Nicholas A.; Licence, Peter
Abstract : The charge distribution associated with individual components in functionalised ionic liquids (ILs) can be tuned by careful manipulation of the substituent groups incorporated into the ions. Abstract : The charge distribution associated with individual components in functionalised ionic liquids (ILs) can be tuned by careful manipulation of the substituent groups incorporated into the ions. Here we use X-ray photoelectron spectroscopy to investigate the impact of substituent atoms on the electronic structure of similar imidazolium-based systems each paired with a common anion, [Tf2 N] − . The experimental measurements revealed an unexpected variation in the charge density distribution within the IL cation when the oxygen atom in a poly-ether containing side chain is moved by just one atomic position. This surprising observation is supported by density functional theory calculations.